ANALISIS MINERAL KALSIUM (Ca) DAN ZAT BESI (Fe) DENGAN VARIASI WAKTU PERENDAMAN PADA PEMBUATAN SUSU KEDELAI SECARA SPEKTROFOTOMETRI SERAPAN ATOM - Eka Margaret Sinaga; Yosy Cinthya Eriwaty Silalahi; Artha Yuliana Sianipar (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Minerals, calcium, and iron are needed for humans to stay healthy and active and have various roles in the human body. The purpose of this study was to determine the levels of calcium and iron in SK1, SK2, SK3, and SK4 milk. To compare calcium and iron levels in SK1, SK2, SK3, and SK4 milk. The results of the determination of calcium and iron levels by atomic absorption spectrophotometry showed that there was a difference in the content of calcium and iron in SK3 soy milk (12.178 ± 46, 399 mg/100 ml), SK1 milk (5, 3008 ± 8, 798 mg/100). ml), SK2 milk (9, 8821 ± 55, 676 mg/100 ml), SK4 milk (4, 8634 ± 125, 845). The iron content of SK4 milk is (1.3851 ± 82.709 mg/100 ml), SK1 milk is (0.5501 ± 68.924 mg/100 ml), SK2 milk is (0.6450 ± 50.026 mg/100 ml), SK3 milk of (0.7464 ± 64 mg/100 ml). The results showed that SK3 soy milk contained more calcium than SK1, SK2, and SK4. The results of iron levels showed that SK4 soy milk contained greater iron than SK1, SK2, and SK3 soy milk.